Tahajud, Spiritualitas, dan Kesehatan Perempuan Hamil - Amirudin Amirudin (CV Kalimasada Group, 2026)
Spirituality is a two-dimensional concept: a vertical dimension comprising one’s relationship with God that guides life, and a horizontal dimension comprising one’s relationship with oneself, others, and the environment. This article examines the relevance of spiritual practice, particularly the tahajjud night prayer, to the health of pregnant women. The study employs a qualitative approach using library research on literature in midwifery, health psychology, and Islamic scholarship, analyzed descriptively and analytically. The findings show that pregnancy triggers hormonal and psychological changes that often generate anxiety and even depression, so that the spiritual dimension becomes a need that cannot be neglected in health care. Prayer—including the sunnah tahajjud prayer—may provide psychological calm as well as physical benefits through the movements of bowing and prostration, as suggested by several studies on the influence of spirituality during pregnancy. Tahajjud in particular carries spiritual virtues that can foster calm, optimism, and total reliance (tawakkul) in pregnant women. The study concludes that integrating the spiritual dimension into midwifery care standards, within a “bio-psycho-socio-spiritual” framework, is important to support the well-being of both mother and fetus.